Ignorancia(s) - Laura Barbier; Soraya Boudia; Maël Goumri; Justyna Moizard-Lanvin (Revue d'anthropologie des connaissances)
For over twenty years, ignorance has been a thriving research topic in sociology, philosophy, history, and anthropology, leading to a rich body of literature. This article critically rethinks the contributions and limitations of ignorance studies. It aims to provide an account of findings from studies of ignorance from agnotology, the new political sociology of science, and the study of strategic ignorance, and to document developments in their research questions and what they excluded or left in the shadows. Based on this analysis, the article then proposes overcoming their limitations by further pursuing some paths opened by ignorance studies and by widening the focus to renew and expand the study of ignorance, working to clarify the complex dynamics that connect ignorance, knowledge, and uncertainty in a variety of configurations.